Effect of Sampling Orientation on The Mechanical Properties of Glass Fiber Reinforced Epoxy Nanocomposites - Gökhan Demircan (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Fiber-reinforced polymer composites are manufactured using various methods, with vacuum-assisted resin transfer molding (VARTM or VARIM). This study's primary focus lies in assessing how the orientation of sampling impacts the mechanical properties of glass fiber-reinforced pure and nanocomposites. 2 wt.% nano Al2O3-doped and non-doped composites were produced using the VARTM process. Tensile, flexural, and density test specimens were extracted from three distinct zones and two distinc direction those aligned horizontally to the resin flow (HRF) and those oriented vertically to the resin flow (VRF). Remarkably, results showed up to a 3.91% increase in values from samples in the third zone, particularly on the vacuum outlet side. To facilitate precise stress value comparisons across plates, uniform sample orientation and consistent zone selection are essential.